1998
DOI: 10.1038/sj.bmt.1701174
|View full text |Cite
|
Sign up to set email alerts
|

Early intensive therapy with autologous stem cell transplantation in advanced Hodgkin’s disease: retrospective analysis of 158 cases from the French registry

Abstract: This retrospective study was undertaken to evaluate cure rates, toxicity and late effects of early intensive therapy followed by autologous stem cell transplantation (ASCT) in patients with advanced Hodgkin's disease (HD). One hundred and fifty-eight cases of ASCT registered in the French database (SFGM) were retrospectively analyzed. Disease status at the time of ASCT was first partial response (PR) in 85, first complete remission (CR1) in 45 or primary refractory in 28 cases. The median time interval between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…We did not find a significant difference in EFS rates according to disease status at the time of ASCT, probably because of the small size of this group, since status at transplantation has been proven to be a significant prognostic factor in larger series of adult patients. 6,14,15,17 No randomized studies comparing the effectiveness of ASCT vs standard chemotherapy in relapsed children with HD have been reported. Despite the fact that the follow-up time in our series of patients is not yet very long, the overall outcome is encouraging with an overall survival of 0.95 and EFS rate of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a significant difference in EFS rates according to disease status at the time of ASCT, probably because of the small size of this group, since status at transplantation has been proven to be a significant prognostic factor in larger series of adult patients. 6,14,15,17 No randomized studies comparing the effectiveness of ASCT vs standard chemotherapy in relapsed children with HD have been reported. Despite the fact that the follow-up time in our series of patients is not yet very long, the overall outcome is encouraging with an overall survival of 0.95 and EFS rate of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,8,10,[12][13][14]17,18,20,21,38,[43][44][45][46][47][48][49] In a study of 65 patients with relapsed or refractory HD, Moskowitz found that B symptoms, extranodal disease and less than 1 year remission duration were all adverse prognostic indicators. 50 A French registry study of 280 patients with HD found chemosensitive disease and first relapse to be good prognostic indicators for survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the nonrandomized control group, with a median follow-up of 89 months, 33% were free of disease. Results of other studies looking at this question are presented in Table 3 [32,[39][40][41]. Because of the significant cure rate with standard-dose therapy in even high-risk patients, this approach is controversial.…”
Section: Hdmentioning
confidence: 99%